Developing a Nurse‐Delivered Frenulotomy Service. (22nd October 2014) - Rose, Katie; Kasbekar, Anand V.; Flynn, Alison; De, Sujata
Abstract : Objectives: Tongue tie (ankyloglossia) describes a short lingual frenulum that can lead to breastfeeding difficulties. It affects between 4% and 10% of infants and can be treated by frenulotomy. We developed a nurse‐delivered frenulotomy service at a tertiary pediatric hospital and audited our results. Study Design: Observational study. Setting: Tertiary pediatric hospital. Subjects and Methods: An outpatient tongue tie clinic was set up by an ear, nose, and throat consultant. Tongue tie division was undertaken using a standard technique without the need for anesthesia or analgesia, as per National Institute for Health and Care Excellence guidelines. Subsequently, a senior nurse was trained to undertake the clinic independently and saw most referrals. Patient satisfaction data were collected via questionnaires. Results: Referrals to the service increased from 57 (2009) to 296 (2012). Outcome data from outpatient frenulotomy are discussed. Parent satisfaction measures were similar for both nurse‐ and doctor‐delivered treatment. If all frenulotomies were undertaken in nurse‐delivered clinics, a total of £3830 could have been saved in 2012, compared with the cost of doctor‐delivered care. Conclusion: A nurse‐delivered outpatient frenulotomy service is a safe and cost‐effective method of delivering such care. We have demonstrated reduced costs and reduced waiting times without compromising patient satisfaction or the quality of care provided.